2016
DOI: 10.1007/s00062-016-0528-x
|View full text |Cite
|
Sign up to set email alerts
|

Transluminal angioplasty and stenting versus conservative treatment in patients with symptomatic basilar artery stenosis

Abstract: In this retrospective study we could not reproduce the findings from large RCTs on intracranial stenting. Our data could be considered as a basis for a prospective study on patient selection for PTAS in the basilar artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 20 publications
0
18
1
Order By: Relevance
“…Although the results of both the SAMMPRIS and VISSIT (the Vitesse Intracranial Stent Study for Ischemic Stroke Therapy) trials supported the use of aggressive medical management as being superior to stent therapy ( 6 , 8 ), some prospective and retrospective studies from both Europe and Asia reported encouraging results for endovascular treatment ( 9 14 ). In this article, we will review the current literature related to angioplasty or stent placement for ICAS and discuss the current debate regarding three aspects: patient-, intervention-, and operator-related factors.…”
Section: Introductionmentioning
confidence: 99%
“…Although the results of both the SAMMPRIS and VISSIT (the Vitesse Intracranial Stent Study for Ischemic Stroke Therapy) trials supported the use of aggressive medical management as being superior to stent therapy ( 6 , 8 ), some prospective and retrospective studies from both Europe and Asia reported encouraging results for endovascular treatment ( 9 14 ). In this article, we will review the current literature related to angioplasty or stent placement for ICAS and discuss the current debate regarding three aspects: patient-, intervention-, and operator-related factors.…”
Section: Introductionmentioning
confidence: 99%
“…The use of stents carries some limitations. The risks and complications associated with this treatment options include periprocedural risks of ischaemia, haemorrhage, intimal dissection, postoperative neurological deficits, and the possibility of in-stent restenosis [5, 7, 11, 12]. Additionally, another periprocedural risk is BA branch occlusion due to the “snowploughing” effect (displacing plaque into branch/perforating arteries during the process of stent deployment) in branches such as the anterior inferior cerebellar artery or the pontine arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Emergent thrombectomy results in better recanalisation rates and clinical outcomes compared to intravenous or intra-arterial thrombolysis [4]. Transluminal angioplasty and stenting of symptomatic BA stenosis reduces stroke recurrence, clinically relevant restenosis, progression, and death [5]. We report a case of acute stroke due to BA occlusion successfully treated with emergency thrombectomy followed by immediate BA stenting.…”
Section: Introductionmentioning
confidence: 99%
“…However, neither of these methods is efficacious. Conservative management typically includes modification of systemic arterial hypertension, glucose intolerance, serum lipid profile and treatment with antithrombotic agents [ 3 ]. Surgical management of symptomatic vertebral disease includes subclavian vertebral roof-patch angioplasty, reimplantation of the vertebral origin, carotid-vertebral vein bypass and vertebral ostial endarterectomy [ 4 ].…”
Section: Introductionmentioning
confidence: 99%